Sistem Handling Complain dalam Event Outing Corporate: Complaint Handling System in Corporate Outing Events - Muhammad Heykal; Taufik Ridwan; Ratih Dwi (OGZ Research & Publishing, 2025)
Abstract: A corporate outing is an activity held by a company for its employees outside the office, typically for recreational, educational, or team-building purposes. Outings are a way for the company to show its support for its employees, helping them to boost their morale and build teamwork. The goals of outings are generally related to improving team performance, building better communication, and creating a positive work environment. Objectives: This study aims to achieve two primary goals. First, it seeks to empirically analyze the influence of service quality dimensions. Second, it aims to evaluate the overall performance of the event organizer based on key indicators, including logistical success, communication effectiveness, and overall participant experience. Methodology: Using a quantitative approach, we conducted interviews with event organizers. Research Results: Based on the researcher's interview with Ms. Fathiya, Head of the Administration & Public Relations Division, the complaint handling method used when complaints come in is either in person or via WhatsApp. Complaint handling is indeed a crucial part of this Corporate Outing activity. This means that complaints are not only submitted via social media or the internet, but also through face-to-face discussions.